Hydroxylation of the silica in microfabricated thin layer chromatography plates as probed by time‐of‐flight secondary ion mass spectrometry and diffuse reflectance infrared Fourier transform spectroscopy. (27th November 2014) - Kanyal, Supriya S.; Singh, Bhupinder; Cushman, Cody V.; Jankowski, Daniel T.; Linford, Matthew R.
<x xml:space="preserve">Abstract</x> Microfabricated silica thin layer chromatography (TLC) plates have previously been prepared on patterned carbon nanotube forests. The high temperatures used in their fabrication reduce the number of hydroxyl groups on their surfaces. Fortunately, silica can be rehydroxylated. In diffuse reflectance infrared Fourier transform spectroscopy (DRIFT), a silanol peak below 3740 cm−1 indicates a well‐hydroxylated silica surface that is fit for chromatography. Hydroxylations of our materials with HF are so effective that it is not possible to discern the position of this peak. In contrast, this signal is discernable when the plates are treated with NH4OH. To find a more convenient method for studying the surfaces of TLC plates, time‐of‐flight secondary ion mass spectroscopy (ToF‐SIMS) was considered. ToF‐SIMS is advantageous because multiple microfabricated TLC plates must be scraped to obtain enough silica for one DRIFT analysis, while static SIMS can be performed on very small regions (500 × 500 µm2 or less) of individual plates. Ratios of the SiOH+ and Si+ ToF‐SIMS signals for microfabricated TLC plates correlated well with ~3740 cm−1 silanol peaks from DRIFT. Thus, SIMS allows direct analysis of all of our treated and untreated plates, including those hydroxylated with HF. The best hydroxylation condition for HF, which was better than any studied for NH4OH, was around 150 ppm at room temperature. The best hydroxylation condition for NH4OH was 50 °C for 72 h. ToF‐SIMS versus DRIFT results of commercial TLC plates were also obtained and evaluated. Copyright © 2014 John Wiley & Sons, Ltd.